2018
DOI: 10.17294/2330-0698.1588
|View full text |Cite
|
Sign up to set email alerts
|

Problems Experienced in the First Month After Discharge From a Heart Failure-Related Hospitalization

Abstract: Part of the Cardiology Commons, Cardiovascular Diseases Commons, Cardiovascular System Commons, and the Dietetics and Clinical Nutrition Commons Journal of Patient-Centered Research and Reviews (JPCRR) is a peerreviewed scientific journal whose mission is to communicate clinical and bench research findings, with the goal of improving the quality of human health, the care of the individual patient, and the care of populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…2 Research indicates IHF experience various problems during the first month after a HF hospitalization. 3 Multiple HF symptoms (eg, fatigue, dyspnea on exertion, edema) 4-5 and a multifaceted treatment regimen (eg, numerous medications, a low sodium diet, and daily weights) often impact activities of daily living and self-care. 6 IHF experience psychosocial problems (eg, depressive and negative emotions and moods) as well as financial issues.…”
Section: Brief Reportmentioning
confidence: 99%
See 3 more Smart Citations
“…2 Research indicates IHF experience various problems during the first month after a HF hospitalization. 3 Multiple HF symptoms (eg, fatigue, dyspnea on exertion, edema) 4-5 and a multifaceted treatment regimen (eg, numerous medications, a low sodium diet, and daily weights) often impact activities of daily living and self-care. 6 IHF experience psychosocial problems (eg, depressive and negative emotions and moods) as well as financial issues.…”
Section: Brief Reportmentioning
confidence: 99%
“…6 IHF experience psychosocial problems (eg, depressive and negative emotions and moods) as well as financial issues. 3 Inadequate social support, 7 social isolation, 8 and diminished relationships with family members also are problematic. 3 Yet, little is known about whether these problems change over time.…”
Section: Brief Reportmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent qualitative study of weight management in African American type 2 diabetics (of whom 10 of 12 were women) indicated that social support was the "most effective strategy for weight management when problems, stress, and challenges occur." 15 Heart failure (HF) is another chronic disease for which patient self-management is deemed important, 16,17 although a recent meta-analysis reported that no single intervention program characteristic could have an impact on all common clinical endpoints, nor was any program characteristic clearly associated with better outcomes of HF self-management interventions. 18 Following up a previous publication, 19 Grant and Graven add to this theme issue with a mixed-methods study of patient experiences in months 2 and 3 following hospitalization for HF.…”
Section: T His Spring In Volume 5 Issue 2 Of the Journal Of Patientmentioning
confidence: 99%